Lightweight and dynamic authenticated key agreement and management protocol for smart grid - Zhai, Feng; Yang, Ting; Sun, Wei; Fang, Xu (Frontiers in Energy Research, 2023)
With the development of IoT and 5G, the smart grid, as one of the key component for the smart city, can provide the uninterrupted and reliable electricity service by properly adjusting the electricity supply according to the consumption of users. The advanced metering infrastructure (AMI), as an important part of smart grid system, is a complete network and system for measuring, collecting, storing and analyzing the electricity consumption information of users. The security of AMI plays a vital role in the smooth operation of smart grid. In this paper, we study how to establish the secure communication between two entities in the AMI, namely the smart meter and the electricity service provider. Although, there are many authentication and key management protocols for AMI, the high complexity and computation overhead of these protocols hinder its application in the smart grid environment. Based on identity cryptosystem and elliptic curve, we put forward a lightweight and dynamic authenticated key agreement and management protocol, which can significantly reduce the computation overhead of the resource-constrained smart meters. In addition, we utilize an one-way key tree technique to efficiently generate and update the group key in the multicast communication. We give a systematic proof to show that our designed protocol not only guarantees the confidentiality and integrity of transmitted messages, but also resists various attacks from an adversary. Finally, we carry out some simulated experiments to demonstrate the high efficiency of our designed protocol.